Developing A Communications IC Design Curriculum - Paarmann, L.D.; Kwon, H.M. (2007 IEEE Region 5 Technical Conference, 2007)
Communications integrated circuits is a somewhat interdisciplinary area of research and development, and a somewhat interdisciplinary instructional area as well. Circuit design of communications circuits requires a good background in basic circuit design and analysis, electronic circuit design and analysis, active devices, especially CMOS devices, design and analysis of CMOS integrated circuits, design and analysis of RF integrated circuits, and a good working knowledge of specialized software for IC design and layout. Clearly, knowledge is also necessary in communications systems theory and signal processing. Given initial expertise in communications systems theory, signal processing, and circuit design, but with little collaboration among the three areas, this paper attempts to address the requirements that are necessary to develop a communications IC design research program and curriculum. The questions addressed include: (1) How should existing courses perhaps be modified to stress collaboration? (2) What new courses are perhaps required? (3) What software tools are essential? (4) What lab equipment is needed? The goal of such a development program is to attempt to address critical issues up front during the initial phase so as to be able to make long range plans for growth and development in this area. Part of this initial phase is to identify subjects and research projects that are the easiest to begin with, with prospects of good results. In addition, plans need to be in place for growth and development.